2020
DOI: 10.3390/ijerph17176263
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, Predictors of and Motivation for Quitting among Smokers from Six European Countries from 2016 to 2018: Findings from EUREST-PLUS ITC Europe Surveys

Abstract: The European Tobacco Products Directive (TPD) was introduced in 2016 in an effort to decrease prevalence of smoking and increase cessation in the European Union (EU). This study aimed to explore quitting behaviours, motivation, reasons and perceptions about quitting, as well as predictors (reported before the TPD implementation) associated with post-TPD quit status. A cohort study was conducted involving adult smokers from six EU countries (n = 3195). Data collection occurred pre-(Wave 1; 2016) and post-(Wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
(67 reference statements)
2
7
0
Order By: Relevance
“…Patients who had previously attempted to QS were more likely to succeed than those trying for the first time. Previous attempts to QS were identified an independent predictor in this study, which is consistent with the results of previous studies in China and Europe 11 , 24 . Chaiton et al 25 reported that an average of 30 attempts to QS is associated with the success of QS at one year or longer.…”
Section: Discussionsupporting
confidence: 92%
“…Patients who had previously attempted to QS were more likely to succeed than those trying for the first time. Previous attempts to QS were identified an independent predictor in this study, which is consistent with the results of previous studies in China and Europe 11 , 24 . Chaiton et al 25 reported that an average of 30 attempts to QS is associated with the success of QS at one year or longer.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Kale et al 27 , the only variable in the multivariate analysis that was associated with and predicted abstinence at three months was having a pathology related to tobacco use. In these previous studies, motivation was associated with the attempt to quit smoking but not with the maintenance of abstinence, which has also been observed by other investigators 6 , 12 - 14 , 28 .…”
Section: Discussionsupporting
confidence: 76%
“…A cohort study of adult smokers in six European Union countries showed that focus on individual health and paying close attention to related diseases caused by smoking were important reasons for quitting smoking. Factors such as affecting the health of non-smokers, health care professionals' advice, and the opposition of friends and family were considered important reasons to stop smoking, but were not successful predictors of SC ( 54 ). Thomas et al ( 55 ) believed that health problems were one of the most common reasons for smokers to quit, and while the reasons to quit could not predict ultimate success in SC, it led the smoker to continue to try to quit.…”
Section: Discussionmentioning
confidence: 99%